Consumption of aqueous extract of raw aloe vera leaves: histopathological and biochemical studies in rat and tilapia (2005)
"Forty-five juvenile tilapia and 30 weanling albino rats exposed to water containing 50, 100 and 150ppm of aqueous extract of Aloe vera leaves for 96 hours and 28 days, respectively were used for this study. Fifteen tilapia and 10 rats exposed to clean water (0 ppm A. vera) served as controls. Clinical signs, mortality, gross and histologic organ pathology in the tilapia; weekly haematology, plasma biochemical parameters and organ pathology were monitored in the rats. Fish cultured in water containing A. vera exhibited erratic swimming patterns, rapid opercular movements, skin depigmentation and died within 24- 96 hours. Gross and histologic tissue lesions in the test fish include skin depigmentation, pale and shriveled gills, dull, opaque and sunken eyes, stunting and clubbing of gill filaments, vacuolar degeneration and necrosis of gill epithelial cells, hyaline degeneration and necrosis of myofibrils, calcification of vasa vasori, hepatocellular vacuolar degeneration and necrosis. Haematologic and plasma biochemical changes in test rats include moderate to severe normocytic normochromic anaemia, hypoproteinaemia, increased AST levels, and decreased cholesterol and triglyceride levels. Gross and histologic tissue lesions include mild to moderate pulmonary congestion, flabbiness of the heart, hepatomegaly, mottling of kidneys, vacuolar degeneration and necrosis of hepatocytes, Kupffer cell hyperplasia, periportal fibrosis, glomerular and tubular degeneration and necrosis, matting and clubbing of small intestinal villi, catarrhal enteritis and goblet cell hyperplasia. The severity of these changes increased with increasing concentrations of A. vera. No mortality, gross or histologic changes were observed in both control fish and rats. Results from this study show that consumption of water containing extracts of raw A. vera is very toxic to fish and rats. The serious health implication for human consumption of raw A. vera is discussed. "